Why does higher education sometimes lead to unhappiness in China? An explanation from housing assets - Wu, Yidong; Zhao, Renjie; Zhang, Yalin; Chen, Zhuo (Frontiers in Psychology, 2022)
This paper aims to examine whether higher education would lead to happier life in China, and try to provide some explanations from the perspective of housing asset. Using data from four waves of China Household Finance Survey (CHFS), we find that higher education on average is significantly negatively correlated with people’s happiness in urban China. Considering the booming housing market in urban China, we find that housing asset plays the role in the relationship between higher education and happiness. Specifically, years of schooling could evidently compress the years of being homeowners, as a result, highly educated people generally have more unpaid housing debts and bear more housing purchase costs due to the soaring housing prices. Meanwhile, higher education has negative effect on people’s happiness in cities with relatively high housing prices, while this effect is insignificant in cities with relatively low housing prices. Moreover, the market-oriented housing reform that launched in 1998 has negative impact on highly educated people’s happiness, since it has dramatically boosted housing prices and essentially changed housing distribution system for urban employees. Besides, we also find that Ph.D graduates are the relatively unhappiest people compared to bachelors or masters. Our findings have important policy implications for Chinese government to understand and resolve the “education-happiness paradox”.